Simple predictive models for track and field world placing - Scott, C. (The World through data, 2018)
I decided to test a novel methodology for predicting 100 meter and 110 meter hurdler medalists in the the 2017 World Championships. Specfically, I wanted to builder a model that predicted both placing and the probability of medaling. I decided to predict these odds based on each athlete`s results during the 2017 track and field season. In order to test the validity of this approach, I built a model for each World Championship year from 2005 to 2017. I scraped the IAAF website for all 2005-2017 outdoor results (https://www.iaaf.org/records/toplists/sprints/).